Perceptions of commerce graduates from a selected higher education institution - Kaliika, Michael (Rhodes University, Faculty of Commerce, Department of Management, 2012)
The role of higher education in developing human capital and contributing to economic growth, competitive advantage and societal progress of any country is well documented. The direct link between the economic performance of a country and the level of education of its citizens cannot be repudiated. Furthermore, the demands of a growing economy, governmental pressure and the competitive international business environment have put pressure on South African businesses. This is aggravated by a "skills crisis" and the need to deliver more goods and services to increasingly more diverse customers. There is consensus amongst experts that the shortage of skills and high-level managerial human resources in South Africa constitute a major threat to the country's future economic development and productivity growth. As the business world becomes increasingly sophisticated and challenging, so does the need to continuously review and assess the business qualifications that equip managers to cope with the challenges facing them. The competencies that come with a Commerce degree are relevant in every corner of society from managing successful private companies, public organisations, for governments to be able to contribute to the greatest good of society, to socially effective not- for- profit organisations. Despite the importance of a degree in Commerce there are some criticisms about the degree and Commerce graduates. The problem statement of this study is therefore vested in the continuum of praise and criticisms of Commerce graduates and the Commerce curriculum and, the reported imbalances between higher education institutions and the needs of the labour market. The question is whether such praise and criticisms are justified and whether higher education institutions specifically meet the requirements and expectations of both the graduates themselves and of business practice. The primary research objective of this study was, therefore, to obtain the opinions of Commerce graduates and Commerce graduate employers on the overall perception of Commerce graduates produced by a prominent HEI in the Eastern Cape Province in South iv Africa. To achieve this objective and based on in-depth analysis of secondary sources, two independent empirical surveys, aimed at two population strata were conducted, namely: "¢ The Commerce graduates with known email addresses (N = 1 870) were extracted from the HEI's alumni database. A total of 231 usable questionnaires were received from these Commerce graduates. "¢ The employers with known addresses (N = 85) were extracted from the selected HEIs Career Centre database. A total of 47 usable questionnaires were received from the employers of the Commerce graduates. The main findings in this research pertain to aspects concerning core courses in the Commerce curriculum offered by the selected HEI, management skills and traits as required in the work environment, commerce curriculum outcomes and perceived experience as a student in the Faculty of Commerce at the selected HEI and Employer perceptions on the profile of the Commerce graduate. In this regard, the main findings are therefore summarised below: "¢ Both graduates and employers assigned high relative importance scores to seventeen of the 19 core courses, supporting the multi-functionary interdisciplinary approach to the Commerce curriculum. Concerns were expressed by the Commerce graduates with the quality of tuition they had received in most of the core courses. Likewise, employers were not always satisfied with the Commerce graduates' proficiency in some of the core courses, relative to the importance of core courses for running a business. "¢ The Commerce graduates and employers strongly endorsed and supported the importance of the 43 management skills and traits in the work environment. Commerce graduates expressed concerns about the extent to which their management skills and traits had been developed through tuition. Concerns about the proficiency of the Commerce graduates in all the management skills and traits, relative to the importance in the work place, were conveyed by the employers. "¢ On average the perceptions on the outcome of studies in the Faculty of Commerce were very highly regarded by the Commerce graduates. The highest mean score was for the item "Studying in the Faculty of Commerce contributed to an increase in my knowledge and abilities." "¢ The perceived experience of Commerce graduates as students in the Faculty of Commerce at the selected HEI was very highly regarded, implying that the selected HEI was meeting the expectations of its Commerce graduates. "¢ Employer perceptions of what would constitute an ideal Commerce graduate were not fully met by the profile of the actual Commerce graduate from the selected HEI.
Keywords: Education, Higher -- Curricula -- South Africa -- Evaluation; Business education -- Curricula -- South Africa -- Evaluation; Business education graduates -- South Africa -- Attitudes